Synthesis and flash sintering of (Hf1-xZrx)B2 solid solution powders. Issue 4 (April 2021) - Belisario, Jose; Mondal, Santanu; Khakpour, Iman; Franco Hernandez, Alexander; Durygin, Andriy; Cheng, Zhe
Abstract: (Hf1-x Zrx )B2 solid solution powders were synthesized by two methods. First, solution-based processing of HfCl4, ZrCl4, sucrose, and H3 BO3 was conducted followed by heat treatment in Argon to carry out the carbothermal reduction (CTR) reaction to form the diboride powders. Alternatively, in the so-called borohydride reduction (BHR) method, HfCl4, ZrCl4 and NaBH4 were mixed in an Argon glove box followed by heat treatment in Argon at 700−1500 °C. The synthesized powders were characterized by XRD, SEM, TEM, EDS, and TGA, and the influence of different parameters such as starting composition, heat treatment temperature and time on products characteristics were revealed. Both CTR and BHR solid solution powders were then consolidated within ∼5 min in a homemade flash sintering (FS) setup. The composition, microstructure, hardness, and thermal-oxidation properties of flash sintered ceramics were characterized, and the implication of this study and directions for future research were discussed.